Rethinking Intramuros: Threats, Values, and Possibilities in Modern Philippines - Hsieh, Ellen (Nakhara : Journal of Environmental Design and Planning, 2013)
Intramuros, a walled historic Spanish urban landscape in the Philippines, is located at the heart of Metro Manila. Like most of the developing countries in Asia, Intramuros has faced serious confl icts between urban development and cultural preservation. This paper illustrates the full range of threats to Intramuros, including both natural and human factors, and reexamines the value of Intramuros in the Filipino context. According to these discussions, several recommendations will be given. Furthermore, the basic restoration policy of Intramuros will be questioned. The author calls for applying a wider interpretation to the cultural heritage management of the site.